Puromycin을 투여한 백서에서 지질 변화가 신증의 진행에 미치는 영향 - 최광해; 정효석; 김용진; 하정희; 김흥식; 박용훈; Choi Kwang-Hae; Chung Hyo-Seuk; Kim Yong-Jin; Ha Jeong-Hee; Kim Heung-Sik; Park Yong-Hoon (Journal of the Korean Society of Pediatric Nephrology, 2003)
Purpose : Several studies have suggested that hyperlipidemia might be a causative factor contributing to the progression of initial glomerular injury through the development of glomerulosclerosis. We examined the potential beneficial effect of atorvastatin - which blocks the rate limiting step of cholesterol synthesis by inhibiting HMG-CoA reductase - in PAN-induced nephrosis. Materials and Methods : Glomerulosclerosis was induced in Sprague-Dawley male rats by repeated administration of PAN. Sprague-Dawley male rats were divided into 3 groups : group I(control), group II(PAN 20 mg/kg, subcutaneous injection), group III(PAN 20 mg/kg subcutaneous injection and atorvastatin 50 mg/kg/day per oral). On the 11th week, upon sacrifice of the experimental animals, blood sampling, 24-hr urine collection and nephrectomy were performed. Results : Group III had significantly lower BUN and higher serum albumin($30.9{\pm}17.2\;vs.\;17.3{\pm}2.5\;mg/dL;\;2.3{\pm}0.1\;vs.\;2.5{\pm}0.2\;g/dL$, P<0.05) compared with group II. In the lipid profiles, group III was associated with a reduction in total cholesterol and LDL($291{\pm}173\;vs.\;167{\pm}72\;mg/dL:\;57{\pm}53\;vs.\;27{\pm}12\;mg/dL$, P>0.05) compared with group II. Atorvastatin administration lowered the glomerular sclerosing index significantly(26.2% vs. 13.3%, P<0.05). Conclusion : Puromycin-induced glomerulosclerosis could be ameliorated by the reduction of hyperlipidemia with atorvastatin. This suggests that hyperlipidemia contributes to the pathogenesis of glomerulosclerosis. 목적 : PAN-induced nephrosis 쥐 모델에서 HMG-CoA reductase inhibitor로 작용하여 콜레스테롤을 낮추는 약제로 알려진 atorvastatin을 투여함으로써, 지질대사에 대한 효과와 지질대사의 변화가 쥐 모델의 신장 변화에 미치는 영향을 알아보고자 하였다. 대상 및 방법 : 수컷 Sprague-Dawley 흰쥐를 사용하여 대조군(I군), PAN 단독 투여군(II군), PAN과 atrovastatin 동시 투여군(III군) 3군으로 나누었으며, PAN은 체중 100 gm 당 2 mg을 첫 피하 주사한 후 1, 3, 5, 7, 9주에 반복하여 피하 주사하였으며, atorvastatin은 체중 100 gm당 5 mg을 물에 녹여 매일 경구 투여하였다. 실험 개시 후 11주에 24시간 소변과 혈액을 채취한 다음 신장을 적출 하였으며, 소변의 protein과 creatinine 그리고 혈청의 albumin, BUN, creatinine, lipid profiles를 측정하고, 신장의 형태학적 변화를 관찰하였다. 결과 : 혈청 총 콜레스테롤은 II군이 $291{\pm}173\;mg/dL$, III군이 $167{\pm}72\;mg/dL$, LDL은 II군이 $57{\pm}53\;mg/dL$, III군이 $27{\pm}12\;mg/dL$로 II군 보다 III군에서 감소하였으나 통계학적으로 유의하지는 않았다. 광학 현미경 검사상 사구체 경화의 빈도는 II군이 26.2%, III군이 13.3%로 II군보다 III군에서 적게 나타났다. 결론 : Atorvastatin을 puromycin과 같이 투여한 경우 총 콜레스테롤과 LDL을 낮추었으며 사구체 경화의 빈도도 감소시킨 것으로 보아 고지혈증이 사구체 경화성 변화에 중요한 원인 중의 하나로 생각된다.